2022
DOI: 10.3389/fmolb.2022.884588
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Prognostic Biomarkers Specifically Expressed in Macrophage in IgA Nephropathy Patients Based on Integrated Bioinformatics Analyses

Abstract: Background: Immunoglobulin A nephropathy (IgAN) is the most common type of primary glomerulonephritis worldwide and a frequent cause of end-stage renal disease. The inflammation cascade due to the infiltration and activation of immune cells in glomeruli plays an essential role in the progression of IgAN. In this study, we aimed to identify hub genes involved in immune infiltration and explore potential prognostic biomarkers and therapeutic targets in IgAN.Methods: We combined the single-cell and bulk transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“… 43 CYBB has been proposed as a primary component of the microbicidal oxidase system of phagocytes. Recent studies have suggested its role in the pathogenesis of immunoglobulin A nephropathy 44 , 45 , though its role in AKI remains unclear. VCAN, a member of the aggrecan/versican proteoglycan family, is involved in cell adhesion, proliferation, migration, and angiogenesis, playing an essential role in tissue morphogenesis and maintenance.…”
Section: Discussionmentioning
confidence: 99%
“… 43 CYBB has been proposed as a primary component of the microbicidal oxidase system of phagocytes. Recent studies have suggested its role in the pathogenesis of immunoglobulin A nephropathy 44 , 45 , though its role in AKI remains unclear. VCAN, a member of the aggrecan/versican proteoglycan family, is involved in cell adhesion, proliferation, migration, and angiogenesis, playing an essential role in tissue morphogenesis and maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…CYBB promotes macrophage in ltration in diabetes nephropathy. On the contrary, inhibiting NOX2 can alleviate podocyte damage and oxidative stress 54 .…”
Section: Discussionmentioning
confidence: 99%
“…IFI44L promoter methylation can be used as a blood biomarker for LN (132)(133)(134). The protein encoded by IL10RA is a receptor for interleukin 10 (IL-10) (135). Overexpression of IL-10 in LN renal tissue and peripheral blood is highly correlated with the onset and activity of LN (136, 137).…”
Section: Correlation Of Degs With Lnmentioning
confidence: 99%